Sp3 hybridization defect adjusted metal-free carbon-based catalyst, preparation method thereof and method for preparing hydrogen peroxide

By using metal-free carbon-based catalyst regulated by sp3 hybrid defects in electrochemical double electron oxygen reduction method, the problems of high energy consumption, low yield and high electrocatalyst cost in H2O2 synthesis process are solved, and efficient and economical H2O2 production, yields significantly improved.

CN119281387AActive Publication Date: 2025-01-10SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411262679.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-10
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

In the prior art, the synthesis of H2O2 by anthraquinone method is complicated and has high energy consumption. The use of expensive platinum-based catalysts leads to serious pollution; the direct synthesis of H2O2 process has low yield and is easy to explode, which hinders large-scale application; Low selectivity and long-term cost are the main obstacles to electrochemical hydrogen peroxide synthesis.

Method used

Develop a metal-free carbon-based catalyst for regulating sp3 hybrid defects. By forming a composite material with activated carbon black and 3,4-ethylenedioxythiophene under the action of an initiator, calcining and acid etching, forming a porous material to improve conductivity Performance and oxygen-containing functional groups are used in electrochemical double-electron oxygen reduction method to produce H2O2.

Benefits of technology

It significantly improves the selectivity and yield of H2O2, has low production cost and simple process, and can produce H2O2 efficiently in a flow electrolytic cell, with a yield of 8300mmol gcat-1h-1, which is better than the existing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281387A_ABST
    Figure CN119281387A_ABST
Patent Text Reader

Abstract

The invention discloses a metal-free carbon-based catalyst for sp3 hybridization defect adjustment, a preparation method thereof and a method for preparing hydrogen peroxide, and relates to the technical field of catalyst and hydrogen peroxide preparation, and the preparation method comprises the following steps: mixing activated carbon black, 3, 4-ethylenedioxythiophene, an initiator and water, reacting, drying to prepare a PEDOT / activated carbon black composite material, calcining in a protective gas atmosphere, and carrying out acid etching to obtain the metal-free carbon-based catalyst for sp3 hybridization defect adjustment. And washing and drying to obtain the product. The method for preparing the hydrogen peroxide comprises the following steps: in a reactor with a proton exchange membrane as a diaphragm, taking a gas diffusion layer as a substrate, loading the catalyst on a cathode, taking solid Ag / AgCl as a reference electrode, taking a platinum sheet as a counter anode, taking potassium hydroxide as an electrolyte, continuously introducing oxygen, and carrying out electrocatalytic reaction to prepare the hydrogen peroxide. The method has the beneficial effects that the selectivity of H2O2, the ORR catalytic activity and the yield of H2O2 are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst and hydrogen peroxide preparation, and in particular to sp 3 A hybrid defect-regulated metal-free carbon-based catalyst, a preparation method thereof, and a method for preparing hydrogen peroxide. Background Art

[0002] Hydrogen peroxide is one of the most widely used environmentally friendly oxidants in chemical synthesis, pulp / paper bleaching, wastewater treatment and disinfection. Currently, the industrial-scale synthesis of H2O2 is highly dependent on the energy-intensive anthraquinone redox reaction. However, the anthraquinone process has complex synthesis steps, large-scale facilities and the use of expensive platinum-based catalysts. The process is energy-intensive and polluting, requires large equipment and expensive catalysts, and is difficult to meet the needs of green and sustainable development. Although the direct synthesis of hydrogen peroxide using hydrogen (H2) and oxygen (O2) as raw materials provides a more direct and atom-economical process to ideally solve the problems associated with the complex anthraquinone pathway, the large-scale application of this technology is hindered by the risks of low H2O2 yield and easy explosion. Therefore, the development of safe, economical and efficient H2O2 is of great application significance in production technology.

[0003] The electrochemical two-electron oxygen reduction reaction is an ideal method for the direct synthesis of H2O2 due to its environmental friendliness, low cost, simple synthesis and relatively simple basic equipment. In recent years, a variety of materials have been studied as 2e-ORR catalysts for the generation of hydrogen peroxide via the 2e-ORR pathway, such as noble metals / alloys, functional (O, N, F, S or B) carbon materials, non-noble transition metals, single atom catalysts (SACs) and molecular complexes. However, the low selectivity and long-term cost of current electrocatalysts are the main obstacles to the success of the electrochemical hydrogen peroxide synthesis pathway. Therefore, addressing these challenges requires the development of efficient electrocatalysts to improve the yield and efficiency of the hydrogen peroxide synthesis process. Carbon-based materials are not only available in large quantities and inexpensive, but their production will bring additional economic and environmental benefits from the perspective of the synthetic process.

[0004] Based on the above analysis, the rational design of metal-free carbon-based catalysts using electrochemical two-electron H2O2 production can alleviate the above-mentioned problems of safe, economical and efficient H2O2 production. Metal-free carbon-based catalysts have extremely high specific areas, providing a large number of defect sites for the functionalization of heteroatoms, significantly exposing the rich active sites of heterogeneous electrocatalysis, and realizing efficient 2e-ORR of high-concentration oxygen-containing active substances. In recent years, people have developed some carbon-based catalysts to increase the production of H2O2. For example, in 2022, Ying Gao et al. prepared ultra-high oxygen-doped carbon-based catalysts for electrochemical H2O2 production with a yield of 10.06 mg·cm -2 ·h· -1, with a Faraday efficiency of 97.7% and good stability for more than 10 hours. In 2023, Xiaoyu Shen et al. prepared an oxygen-rich carbon-based catalyst to produce hydrogen peroxide through electrochemical two-electron oxygen reduction. Within 10 hours, the actual hydrogen peroxide production of the flow cell was as high as 111.18 mg·h -1 cm -2 In 2024, Fangmin Wu et al. prepared a metal-free carbon-based catalyst by doping S, N, and O on graphene nanosheets. The selectivity of H2O2 was as high as 97.4%. At an electrolysis current of 0.3-0.5A, the accumulation of H2O2 reached 732.8-1044.4mg·L -1 ·h -1 Therefore, metal-free carbon-based catalysts are attractive for green H2O2 electrosynthesis. Summary of the invention

[0005] In order to solve the following problems existing in the prior art: First, the anthraquinone method for synthesizing H2O2 has complex steps, large-scale facilities and uses expensive platinum-based catalysts. The process has high energy consumption and serious pollution, and uses large-scale equipment and expensive catalysts, which makes it difficult to meet the needs of green and sustainable development. Second, the direct synthesis of hydrogen peroxide using hydrogen (H2) and oxygen (O2) as raw materials has low H2O2 yield and the risk of explosion, which hinders the large-scale application of this technology. Third, the low selectivity and long-term cost of current electrocatalysts are the main obstacles to the success of electrochemical hydrogen peroxide synthesis. The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and provide a sp 3 Hybrid defect-regulated metal-free carbon-based catalyst and preparation method thereof and method for preparing hydrogen peroxide, that is, providing a sp catalyst with high H2O2 selectivity and high H2O2 yield 3 Hybrid surface defect metal-free carbon-based catalyst and preparation method thereof, and application in electrochemical two-electron oxygen reduction method to produce H2O2.

[0006] The technical solution of the present invention is as follows:

[0007] A first aspect of the present invention provides a sp 3 The preparation method of the hybrid defect-regulated metal-free carbon-based catalyst comprises the following steps:

[0008] The activated carbon black, 3,4-ethylenedioxythiophene, an initiator and water are mixed, reacted and dried to obtain a PEDOT / activated carbon black composite material;

[0009] calcining the PEDOT / activated carbon black composite material under a protective gas atmosphere;

[0010] The calcined PEDOT / activated carbon black composite material is subjected to acid etching, washing and drying to obtain the catalyst.

[0011] Optionally, the mass ratio of the activated carbon black, 3,4-ethylenedioxythiophene and initiator is 0.5-1.5: 0.08-0.12: 0.27-0.36.

[0012] Optionally, the reaction temperature is 30-60° C., and the reaction time is 20-28 h.

[0013] Optionally, the calcination temperature is 750-850° C., the heating rate is 3-7° C. / min, and the calcination time is 2-4 h.

[0014] Optionally, the acid etching is performed in concentrated nitric acid at 55-65° C., the concentration of the concentrated nitric acid is 10-16 mol / L, and the acid etching time is 2-4 h.

[0015] Optionally, the activated carbon black includes EC-600JD, and the initiator includes (NH4)2S2O8.

[0016] The second aspect of the present invention provides a sp prepared by the above method. 3 Hybrid defect-regulated metal-free carbon-based catalysts.

[0017] The third aspect of the present invention provides a use of the above catalyst in the preparation of hydrogen peroxide.

[0018] Optionally, the method for preparing hydrogen peroxide comprises the following steps:

[0019] preparing the catalyst into catalyst slurry;

[0020] A standard three-electrode system is used in a reactor with a proton exchange membrane as a diaphragm, a gas diffusion layer is used as a substrate, the catalyst slurry is loaded on the cathode, solid Ag / AgCl is used as a reference electrode, a platinum sheet is used as a counter anode, 0.05-0.2M potassium hydroxide is used as an electrolyte, and oxygen and electrolyte are continuously introduced during the reaction process to prepare hydrogen peroxide through an electrocatalytic reaction.

[0021] Optionally, the loading amount of the catalyst slurry on the cathode is 0.02 to 0.04 mg·cm -2 The electrocatalytic potential is 0.3-0.5 V vs. RHE, and the oxygen flow rate is 30-50 mL·min -1 The flow rate of the electrolyte is 15-25 mL min -1 .

[0022] The present invention has at least one of the following beneficial effects:

[0023] 1. The present invention provides a sp 3 A hybrid defect-regulated metal-free carbon-based catalyst and a preparation method thereof. The present invention first prepares a composite material with activated carbon black and 3,4-ethylenedioxythiophene under the action of an initiator, and calcines the composite material under a protective gas atmosphere to improve the conductivity of the catalyst and obtain a specific porous material; then acid etching is performed to increase the oxygen-containing functional group content and surface roughness of the P-ACB surface, thereby improving the 2e-ORR performance of the catalyst; the present invention prepares a sp 3 A metal-free carbon-based catalyst with hybrid defect regulation, defect regulation means that the catalyst surface of the present invention contains vacancies. The present invention can adsorb *OOH in the intermediates generated in the 2e-ORR process to the catalyst surface through the vacancies, thereby reducing the free energy required for the formation of *OOH on the carbon surface. Therefore, the present invention enhances the adsorption of *OOH intermediates and reduces the free energy required for the formation of *OOH on the carbon surface, thereby increasing the yield of H2O2; and XPS characterization shows that the catalyst prepared by the present invention forms sp 3 -C carbon-based materials are beneficial to improving the catalytic performance of the catalyst. The synthesis process of the invention is simple, the raw materials used are cheap, and the production cost is low.

[0024] 2. The catalyst of the present invention can be used to prepare hydrogen peroxide. The metal-free carbon-based catalyst prepared by the present invention and regulated by sp3 hybridization defects improves the selectivity of H2O2 and the ORR catalytic activity, and finally improves the yield of H2O2. The yield of the present invention can reach 8300mmol gcat -1 h -1 , which is significantly better than the prior art. Therefore, compared with the prior art, the catalyst of the present invention has a better effect on preparing hydrogen peroxide. In addition, the present invention can directly produce H2O2 on site through a simple flow electrolytic cell device, and the preparation method is simple, convenient, efficient and practical. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is sp in Example 1 of the present invention 3 Flowchart of the preparation of hybrid defect-regulated metal-free carbon-based catalysts.

[0026] Figure 2 This is a schematic diagram of the principle of producing H2O2 by a flow electrolysis cell in Example 1 of the present invention.

[0027] Figure 3 is sp in Example 1 of the present invention 3 XPS characterization of hybrid defect-regulated metal-free carbon-based catalysts.

[0028] Figure 4 sp in Examples 2 to 7 of the present invention 3LSV test graph and H2O2 selectivity data graph of hybrid defect-regulated metal-free carbon-based catalysts, wherein (a) is the LSV test graph of Examples 2 to 3, (b) is the LSV test graph of Examples 4 to 5, (c) is the LSV test graph of Examples 6 to 7, and (d) is the H2O2 selectivity data graph of Examples 2 to 7.

[0029] Figure 5 They are LSV test diagrams and H2O2 selectivity data diagrams of Example 1 and Comparative Examples 1 and 2 of the present invention, wherein (a) is the LSV test diagram of Example 1 and Comparative Examples 1 and 2, and (b) is the H2O2 selectivity data diagram of Example 1 and Comparative Examples 1 and 2.

[0030] Figure 6 It is a comparison chart of H2O2 production data of Example 1 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0031] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0032] An embodiment of the present invention provides a sp 3 The preparation method of the hybrid defect-regulated metal-free carbon-based catalyst comprises the following steps:

[0033] The activated carbon black, 3,4-ethylenedioxythiophene, an initiator and water are mixed, reacted and dried to obtain a PEDOT / activated carbon black composite material;

[0034] calcining the PEDOT / activated carbon black composite material under a protective gas atmosphere;

[0035] The calcined PEDOT / activated carbon black composite material is subjected to acid etching, washing, and drying to obtain a sp 3 Hybrid defect-regulated metal-free carbon-based catalysts.

[0036] The present invention first prepares a composite material with activated carbon black and 3,4-ethylenedioxythiophene, and calcines it under a protective gas atmosphere, which can improve the conductivity of the catalyst and obtain a specific porous material; then acid etching is performed to increase the oxygen-containing functional group content and surface roughness of the P-ACB surface, thereby improving the 2e-ORR performance of the catalyst. The present invention has a simple synthesis process, uses cheap raw materials, and has low production costs.

[0037] In some embodiments, the initiator comprises (NH4)2S2O8.

[0038] In some embodiments, the activated carbon black includes EC-600JD.

[0039] In some embodiments, the mass ratio of the activated carbon black, 3,4-ethylenedioxythiophene, and initiator is 0.5-1.5: 0.08-0.12: 0.27-0.36. Preferably, it is 0.6-1.4: 0.09-0.11: 0.3-0.34. More preferably, it is 0.7-1.3: 0.1: 0.3. Specifically, it can be 0.5: 0.1: 0.3, 0.8: 0.1: 0.3, 1: 0.1: 0.3, 1.2: 0.1: 0.3, or 1.5: 0.1: 0.3, etc.

[0040] In some embodiments, the reaction temperature is 30-60°C, and the reaction time is 20-28h. Preferably, the reaction temperature is 35-55°C, and the reaction time is 22-26h. More preferably, the reaction temperature is 40-50°C, and the reaction time is 23-25h. The reaction temperature can be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, and the reaction time can be 20h, 22h, 23h, 24h, 26h or 28h, etc.

[0041] In some embodiments, the calcination temperature is 750-850°C, the heating rate is 3-7°C / min, and the calcination time is 1-3h. Preferably, the calcination temperature is 770-830°C, the heating rate is 3.5-6.5°C / min, and the calcination time is 1.2-2.8h. More preferably, the calcination temperature is 790-810°C, the heating rate is 4-6°C / min, and the calcination time is 1.5-2.5h. The calcination temperature can be 750°C, 760°C, 780°C, 800°C, 820°C, 840°C or 850°C, etc., the heating rate can be 3°C / min, 4°C / min, 5°C / min, 6°C / min or 7°C / min, etc., and the reaction time can be 1h, 1.5h, 2h, 2.5h or 3h, etc.

[0042] In some embodiments, the acid etching is carried out in concentrated nitric acid at 55-65°C, the concentration of concentrated nitric acid is 10-16 mol / L, and the acid etching time is 2-4 hours. Preferably, the acid etching is carried out in concentrated nitric acid at 56-64°C, the concentration of concentrated nitric acid is 11-15 mol / L, and the acid etching time is 2.2-3.8 hours. More preferably, the acid etching is carried out in concentrated nitric acid at 58-62°C, the concentration of concentrated nitric acid is 13-14 mol / L, and the acid etching time is 2.5-3.5 hours. The temperature of concentrated nitric acid can be 55°C, 58°C, 60°C, 62°C, or 65°C, etc., the concentration of concentrated nitric acid can be 12 mol / L, 13 mol / L, 14 mol / L, or 16 mol / L, etc., and the acid etching time can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, or 4 hours, etc.

[0043] In some embodiments, the drying temperature is 55-65°C, and the drying time is 20-28h. Preferably, the drying temperature is 56-64°C, and the drying time is 22-26h. More preferably, the drying temperature is 58-62°C, and the drying time is 23-25h. The drying temperature can be 55°C, 58°C, 60°C, 62°C, or 65°C, and the drying time can be 20h, 22h, 23h, 24h, 26h, or 28h.

[0044] In some embodiments, the shielding gas includes an inert gas, such as argon.

[0045] Another embodiment of the present invention provides a sp prepared by the above method. 3 Hybrid defect-regulated metal-free carbon-based catalysts.

[0046] The metal carbon-based catalyst of the present invention is a specific porous material, has an oxygen-containing functional group content on the surface, and has a certain surface roughness, can provide 2e-ORR performance, and has high selectivity and high ORR catalytic activity for H2O2.

[0047] Another embodiment of the present invention provides a use of the above catalyst in preparing hydrogen peroxide.

[0048] The catalyst of the present invention can be used to prepare hydrogen peroxide. The metal-free carbon-based catalyst regulated by the sp3 hybridization defect prepared by the present invention can improve the selectivity of H2O2, the ORR catalytic activity and the yield of H2O2.

[0049] In some embodiments, the method for preparing hydrogen peroxide comprises the following steps:

[0050] preparing the catalyst into catalyst slurry;

[0051] A standard three-electrode system is used in a reactor with a proton exchange membrane as a diaphragm, a gas diffusion layer is used as a substrate, the catalyst is loaded on the cathode, solid Ag / AgCl is used as a reference electrode, a platinum sheet is used as a counter anode, 0.05-0.15M potassium hydroxide is used as an electrolyte, and oxygen and electrolyte are continuously introduced during the reaction process to prepare hydrogen peroxide through an electrocatalytic reaction.

[0052] In some embodiments, the method for preparing the catalyst slurry includes: dissolving the catalyst in isopropanol, a dispersant and a deionized water solution, and mixing to obtain a uniform mixture; preferably, the method for preparing the catalyst slurry includes: weighing 1.5 mg of the catalyst and dissolving it in 1150 μL of isopropanol, 35 μL of Nafion (dispersant) and 15 μL of deionized water solution, and ultrasonicating for 1 hour to obtain a uniform mixture.

[0053] In some embodiments, the reactor is a flow electrolysis cell equipped with a separator.

[0054] In some embodiments, the proton exchange membrane is NR211Nafion TM membrane.

[0055] In some embodiments, the gas diffusion layer is a carbon paper containing a microporous layer formed by rolling carbon fiber, carbon powder and PTFE, and the area of ​​the gas diffusion layer is 1.0×1.0 cm 2 .

[0056] In some embodiments, the catalyst loading on the cathode is 0.02 to 0.04 mg·cm -2 The electrocatalytic potential is 0.3-0.5 V vs. RHE, and the oxygen flow rate is 35-45 mL·min -1 The flow rate of the electrolyte is 15-25 mL min -1 Preferably, the catalyst loading is 0.025 to 0.035 mg·cm -2 The electrocatalytic potential is 0.35-0.45 V vs. RHE, and the oxygen flow rate is 37-43 mL·min -1 The flow rate of the electrolyte is 17-23 mL min -1 Preferably, the catalyst loading is 0.03 mg·cm -2 The electrocatalytic potential is 0.4 V vs. RHE, and the oxygen flow rate is 40 mL min -1 The flow rate of the electrolyte is 20 mL min -1 .

[0057] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0058] The following raw materials, activated carbon black, 3,4-ethylenedioxythiophene, (NH4)2S2O8, and concentrated nitric acid, are all commercially available.

[0059] Example 1

[0060] like Figures 1-2 As shown, in this embodiment, a sp 3 A metal-free carbon-based catalyst regulated by hybrid defects is used to prepare H2O2. The specific preparation steps are as follows:

[0061] (1) Disperse 2 g of activated carbon black EC-600JD in 10 mL of deionized water and continue ultrasonication for 3 h to make the activated carbon black EC-600JD evenly dispersed in the deionized water.

[0062] (2) Slowly add 0.2 g of 3,4-ethylenedioxythiophene (EDOT) into the solution.

[0063] (3) Then, 2.8 mmol (NH4)2S2O8 was dissolved in 10 mL of deionized water and added to the above mixture. All samples were mixed evenly and reacted at 50°C for 24 h. Then, the prepared black substance was collected.

[0064] (4) Dry at 60°C for another 24 h, and mark the dried black substance as the PEDOT / EC-600JD composite.

[0065] (5) Then, heat treatment was performed at 800°C (heating rate of 5°C / min) for 2 hours under Ar. The generated dark black substance was recorded as P-ACB.

[0066] (6) The sample was further subjected to an acid etching process in concentrated nitric acid (16 mol / L) at 60°C for 3 hours. It was then washed five times with deionized water and ethanol, respectively. The obtained powder was dried at 60°C for further use and was referred to as HP-ACB.

[0067] (7) Preparation of catalyst slurry: 1.5 mg of catalyst was weighed and dissolved in 1150 μL of isopropanol, 35 μL of dispersant Nafion and 15 μL of deionized water, and ultrasonicated for 1 hour to obtain a uniform mixture.

[0068] (8) Electrochemical test: 6 μL was taken with a pipette and dropped on the RRDE working electrode. Before the test, the working electrode was charged at 50 mV·S -1Cyclic voltammetry was performed for 50 cycles at a scan rate of 1.5 % for electrochemical stabilization. After the catalyst was stabilized, its cyclic voltammetry (CV) curve was collected. The LSV curve of the working electrode was collected at a rotating disk electrode at a speed of 1600 rpm to calculate the H2O2 selectivity of the catalyst.

[0069] (9) Batch production of H2O2: Batch production of H2O2 is carried out using NR211 Nafion TM The flow electrolysis cell was carried out with the membrane as separator. The gas diffusion layer (1.0×1.0 cm 2 ) as a substrate, the catalyst slurry (0.03 mg cm -2 ). The reference electrode is a solid Ag / AgCl electrode, and the platinum sheet is the anode. The test potential is set to 0.4 V vs. RHE, 100 mL of 0.1 M potassium hydroxide is used as the electrolyte, and the oxygen flow rate is 40 mL min -1 , electrolyte flow rate 20mL·min -1 .

[0070] Example 2

[0071] This embodiment provides a sp 3 A hybrid defect-regulated carbon-based catalyst is used to prepare H2O2, which differs from Example 1 in that 2.4 mmol (NH4)2S2O8 in step (3) is dissolved in 10 mL deionized water.

[0072] The other steps are the same as those in Example 1.

[0073] Example 3

[0074] This embodiment provides a sp 3 A hybrid defect-regulated carbon-based catalyst is used to prepare H2O2, which differs from Example 1 in that 3.1 mmol (NH4)2S2O8 in step (3) is dissolved in 10 mL deionized water.

[0075] The other steps are the same as those in Example 1.

[0076] Example 4

[0077] This embodiment provides a sp 3 A hybrid defect-regulated carbon-based catalyst is used to prepare H2O2. The difference between the embodiment 1 and the embodiment 1 is that the calcination temperature in step (5) is 750°C.

[0078] The other steps are the same as those in Example 1.

[0079] Example 5

[0080] This embodiment provides a sp 3 A hybrid defect-regulated carbon-based catalyst is used to prepare H2O2. The difference between the embodiment 1 and the embodiment 1 is that the calcination temperature in step (5) is 850°C.

[0081] The other steps are the same as those in Example 1.

[0082] Example 6

[0083] This embodiment provides a sp 3 A hybrid defect-regulated carbon-based catalyst is used to prepare H2O2. The difference between the embodiment 1 and the embodiment 1 is that the acid etching time in step (6) is 2 hours.

[0084] The other steps are the same as those in Example 1.

[0085] Example 7

[0086] This embodiment provides a sp 3 A hybrid defect-regulated carbon-based catalyst is used to prepare H2O2. The difference between the embodiment 1 and the embodiment 1 is that the acid etching time in step (6) is 4 hours.

[0087] The other steps are the same as those in Example 1.

[0088] Comparative Example 1

[0089] This comparative example provides a sp 3 A hybrid defect-regulated carbon-based catalyst, and the use of the catalyst to prepare H2O2, which is different from Example 1 in that pure activated carbon black without the steps (1) to (4) in Example 1 is used to calcine and acid-etch under the same conditions as the HP-ACB in Example 1 to prepare a catalyst (abbreviated as ACB);

[0090] ACB was then used to prepare H2O2, and the preparation conditions were the same as in Example 1.

[0091] Comparative Example 2

[0092] This comparative example provides a metal-free carbon-based catalyst and uses the catalyst to prepare H2O2. The difference between this comparative example and Example 1 is that concentrated nitric acid is not used for acid etching, that is, step (6) in Example 1 is not performed. The other steps are the same as those in Example 1, and a catalyst (referred to as P-ABC) is obtained.

[0093] P-ABC was then used to prepare H2O2, and the preparation conditions were the same as in Example 1.

[0094] Test results:

[0095] (1) The catalysts prepared in Example 1 and Comparative Examples 1-2 were characterized by XPS. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the catalyst (HP-ACB) prepared in Example 1 is located at C-sp 3 The binding energy of is 285.5 eV, indicating the formation of C-sp 3 Compared with the catalyst prepared in Comparative Example 1 (ACB) and the catalyst prepared in Comparative Example 2 (P-ABC), the C-sp 3 The content is the highest, indicating that the incorporation of C-sp 3 defects improves the catalytic activity of carbon-based electrocatalysts in 2e-ORR.

[0096] (2) Figure 4 (ac) show the LSV curves of the catalysts of Examples 2 to 7. It can be seen from the figure that the amount of (NH4)2S2O8, the calcination temperature and the acid etching time affect the C-sp 3 Hybrid defect-regulated 2e-ORR performance of carbon-based materials. Figure 4 (d) shows that the selectivities of the catalysts of Examples 2 to 6 are 71.64%, 77.11%, 60.17%, 72.57%, 73.77% and 69.20% respectively. The experimental results show that the catalyst prepared under the conditions of Example 1 has high H2O2 selectivity and good catalytic performance.

[0097] The selectivity of the catalysts for H2O2 in Example 1 and Comparative Examples 1-2 is as follows: Figure 5 shown.

[0098] Depend on Figure 5 (a) shows the linear sweep voltammetry (LSV) curves of Example 1 and Comparative Examples 1-2 tested in N2 and O2 saturated electrolytes with a rotating disk electrode at 1600 rpm, wherein the solid line is the LSV curve measured in O2 saturated electrolyte, and the dotted line (current close to zero) is the LSV curve measured in N2 saturated electrolyte. Figure 5 (a) It can be seen that the current of the LSV curve (dashed line) of the catalysts in Example 1 and Comparative Examples 1-2 in N2 saturated electrolyte is close to zero, indicating that the electrocatalytic performance of the three catalysts is weak under N2 saturated electrolyte, that is, they are catalytically inert to 2e-ORR under N2 environment; and it can be seen from the solid line that the three catalysts have good catalytic performance under O2 environment. In addition, the disk current density and ring current density of the LSV curve of Example 1 in O2 saturated electrolyte are greater than those of Comparative Examples 1-2, indicating that compared with Comparative Examples 1-2, Example 1 has better catalytic performance for 2e-ORR under O2 conditions.

[0099] Depend on Figure 5(b) It can be seen that the selectivity of the catalyst in Example 1 to H2O2 is 84.5%, which is significantly greater than the selectivity of Comparative Examples 1-2 to H2O2, indicating that the catalyst prepared by the present invention has a high selectivity to H2O2.

[0100] (3) The yield of H2O2 prepared by the catalyst in Example 1 and Comparative Examples 1-2 is as follows Figure 6 As shown by Figure 6 It can be seen that the catalyst (HP-ACB) in Example 1 produces H2O2 with a yield of up to 8.3 mol gcat -1 h -1 , while the production of H2O2 by the catalyst prepared in Comparative Example 1 (ACB) and the catalyst prepared in Comparative Example 2 (P-ABC) was only 1.30 mol gcat -1 h -1 and 2.90molgcat -1 h -1 , Example 1 is much higher than Comparative Examples 1-2, indicating that the catalyst prepared by the present invention can be used to prepare H2O2 with high yield.

[0101] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A sp 3 A method for preparing a hybrid defect-regulated metal-free carbon-based catalyst, characterized in that: The following steps are involved: The activated carbon black, 3,4-ethylenedioxythiophene, an initiator and water are mixed, reacted and dried to prepare a PEDOT / activated carbon black composite material; calcining the PEDOT / activated carbon black composite material under a protective gas atmosphere; The calcined PEDOT / activated carbon black composite material is subjected to acid etching, washing and drying to obtain the catalyst.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the activated carbon black, 3,4-ethylenedioxythiophene and the initiator is 0.5-1.5: 0.08-0.12: 0.27-0.

36.

3. The preparation method according to claim 1, characterized in that: The reaction temperature is 30-60° C., and the reaction time is 20-28 hours.

4. The preparation method according to claim 1, characterized in that: The calcination temperature is 750-850° C., the heating rate is 3-7° C. / min, and the calcination time is 2-4 hours.

5. The preparation method according to claim 1, characterized in that: The acid etching is carried out in concentrated nitric acid at 55-65° C., the concentration of the concentrated nitric acid is 10-16 mol / L, and the acid etching time is 2-4 hours.

6. The preparation method according to claim 1, characterized in that: The activated carbon black includes EC-600JD, and the initiator includes (NH4)2S2O8.

7. sp prepared by the method according to any one of claims 1 to 6 3 Hybrid defect-regulated metal-free carbon-based catalysts.

8. Use of the catalyst according to claim 7 in the preparation of hydrogen peroxide.

9. The use according to claim 8, characterized in that: The method for preparing hydrogen peroxide comprises the following steps: preparing the catalyst into catalyst slurry; A standard three-electrode system is used in a reactor with a proton exchange membrane as a diaphragm, a gas diffusion layer is used as a substrate, the catalyst slurry is loaded on the cathode, solid Ag / AgCl is used as a reference electrode, a platinum sheet is used as a counter anode, 0.05-0.1M potassium hydroxide is used as an electrolyte, and oxygen and electrolyte are continuously introduced during the reaction process to prepare hydrogen peroxide through an electrocatalytic reaction.

10. The use according to claim 9, characterized in that: The loading amount of the catalyst slurry on the cathode is 0.02-0.04 mg·cm -2 The electrocatalytic potential is 0.3-0.5 V vs. RHE, and the oxygen flow rate is 30-50 mL·min -1 The flow rate of the electrolyte is 15-25 mL min -1 .

Citation Information

Patent Citations

  • Metal-free carbon-based catalyst rich in sp3 hybrid carbon and preparation method thereof

    CN112909275A

  • Composite material, preparation method thereof and luminescent device

    CN113707778A

  • Catalyst, method for production of same, and use of same

    WO2010126020A1